Answer:
f(x) = x³ – 3x² – 10x + 24 = (x + 3)(x – 2)(x – 4)
Explanation:
I would use the Horner method.
f(x) = x³ – 3x² – 10x + 24
f(2) = 2³ - 3·2² - 10·2 +24 = 0 ⇒ x=2 is the root of function
So:
| 1 | -3 | -10 | 24 |
2 | 1 | -1 | -12 | 0 |
therefore:
f(x) = x³ – 3x² – 10x + 24 = (x – 2)(x² – x – 12)
For x² – x – 12:
![x=(1\pm√((-1)^2-4\cdot1\cdot(-12)))/(2\cdot1)=(1\pm√(1+48))/(2)=(1\pm7)/(2)\\\\x_1=(1+7)/(2)=4\ ,\qquad x_2=(1-7)/(2)=-3](https://img.qammunity.org/2021/formulas/mathematics/high-school/7vjohmuw5ewyqzz6r10uuys24zueged59v.png)
It means:
f(x) = x³ – 3x² – 10x + 24 = (x – 2)(x – 4)(x + 3)